Brain regions concerned with the identification of deceptive soccer moves by higher-skilled and lower-skilled players - Wright, Michael; Bishop, Daniel T.; Jackson, Robin; Abernethy, Bruce (Frontiers in Human Neuroscience, 2013)
Expert soccer players are able to utilize their opponents’ early body kinematics to predict the direction in which the opponent will move. We have previously demonstrated enhanced fMRI activation in experts in the motor components of an action observation network (AON) during sports anticipation tasks. Soccer players often need to prevent opponents from successfully predicting their line of attack, and consequently may try to deceive them; for example, by performing a step-over. We examined how AON activations and expertise effects are modified by the presence of deception. Three groups of participants; higher-skilled males, lower-skilled males and lower-skilled females, viewed video clips in point-light format, from a defender’s perspective, of a player approaching and turning with the ball. The observer’s task in the scanner was to determine whether the move was normal or deceptive (involving a step-over), while whole-brain functional images were acquired. In a second counterbalanced block with identical stimuli the task was to predict the direction of the ball. Activations of AON for identification of deception overlapped with activations from the direction identification task. Higher-skilled players showed significantly greater activation than lower-skilled players in a subset of AON areas; and lower-skilled males in turn showed greater activation than lower-skilled females, but females showed more activation in visual cortex. Activation was greater for deception identification than for direction identification in dorsolateral prefrontal cortex, medial frontal cortex, anterior insula, cingulate gyrus, and premotor cortex. Conversely, greater activation for direction than deception identification was found in anterior cingulate cortex and caudate nucleus. Results are consistent with the view that explicit identification of deceptive moves entails cognitive effort and also activates limbic structures associated with social cognition and affective responses